2015
DOI: 10.1088/1367-2630/17/9/093001
|View full text |Cite
|
Sign up to set email alerts
|

A proof of the Kochen–Specker theorem can always be converted to a state-independent noncontextuality inequality

Abstract: Quantum contextuality is one of the fundamental notions in quantum mechanics. Proofs of the Kochen-Specker theorem and noncontextuality inequalities are two means for revealing the contextuality phenomenon in quantum mechanics. It has been found that some proofs of the Kochen-Specker theorem, such as those based on rays, can be converted to a state-independent noncontextuality inequality, but it remains open whether this is true in general, i.e., whether any proof of the Kochen-Specker theorem can always be co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…Connections between contextuality and universal quantum computation [32] and steering [33] that have recently been established ask for a quantification of properties of contextual sets, e.g., robustness to noise [34], size of maximal independent sets of stabilizer states [32], or suitability for implementation in general. It has been shown that inequalities are an efficient tool for the pur-pose [1,30,[35][36][37][38][39][40]. Yu, Guo, and Tong prove [40] that operator formulations of Kochen-Specker contextual sets can always be converted to state-independent noncontextuality inequalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Connections between contextuality and universal quantum computation [32] and steering [33] that have recently been established ask for a quantification of properties of contextual sets, e.g., robustness to noise [34], size of maximal independent sets of stabilizer states [32], or suitability for implementation in general. It has been shown that inequalities are an efficient tool for the pur-pose [1,30,[35][36][37][38][39][40]. Yu, Guo, and Tong prove [40] that operator formulations of Kochen-Specker contextual sets can always be converted to state-independent noncontextuality inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that inequalities are an efficient tool for the pur-pose [1,30,[35][36][37][38][39][40]. Yu, Guo, and Tong prove [40] that operator formulations of Kochen-Specker contextual sets can always be converted to state-independent noncontextuality inequalities. The problem with the inequalities in these references is that either no definite inequality is given or that they were given for chosen particular contextual sets previously specified via sets of vectors/rays, or that they have not been formulated for probabilities applicable to genuine YES-NO quantum experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The KS theorem was proved on the set L(H) of the closed linear subspaces of H such that each pair of the subspaces in L(H) has a meet (greatest lower bound) corresponding to their set-theoretic intersection. Since the original demonstration for |S| = 117 and N = 3, more and more proofs of the KS theorem have been found for the same or higher N but lesser |S| (see [5,6,7,8], to cite but a few examples), and the task has become to reduce the technical difficultness required to prove the KS theorem in order to make the issues involved clearer.…”
Section: Introductionmentioning
confidence: 99%
“…For all other multi-context configurations allowing two-valued states-even with a nonseparable or unital set of two-valued states-the translation from {0, 1}-states into two-valued {−1, 1}-observables there is no state-independent quantum contextuality. For other operator-valued assignments see, for instance, references [4,12].…”
mentioning
confidence: 99%